2016
DOI: 10.1177/1078155215624262
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the leucovorin shortage: Pilot study investigating cost, efficacy, and toxicity comparison of low fixed-dose versus body surface area-adjusted leucovorin dosing in patients with resectable colon or metastatic colorectal cancer

Abstract: Purpose As a result of the leucovorin shortage, we switched from BSA-adjusted to low fixed-dose leucovorin in patients with colon cancer receiving fluorouracil-containing therapy. Methods A retrospective, pilot study of adults receiving intravenous leucovorin as part of a fluorouracil-containing treatment was conducted including individuals with stage II or III colon or newly diagnosed metastatic colorectal cancer. One low fixed-dose (leucovorin 50 mg) patient was matched by the investigator to one BSA-adjuste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…However and interestingly, successive drug shortages have refocused oncology specialists on evidence-based medicine (EBM) [4]. For example, folate shortage has pushed oncology practitioners to experiment a standardized low dose protocol, and first results appear to be consistent with a similar efficacy [5]. After the discovery of paclitaxel as an antimitotic drug, the first clinical trials with paclitaxel have revealed a high rate of HSR (up to 40 %) [7].…”
mentioning
confidence: 99%
“…However and interestingly, successive drug shortages have refocused oncology specialists on evidence-based medicine (EBM) [4]. For example, folate shortage has pushed oncology practitioners to experiment a standardized low dose protocol, and first results appear to be consistent with a similar efficacy [5]. After the discovery of paclitaxel as an antimitotic drug, the first clinical trials with paclitaxel have revealed a high rate of HSR (up to 40 %) [7].…”
mentioning
confidence: 99%
“…Drug shortage problem has become a national health care disaster. It is an increasing crisis in the United States of America (USA) that adversely affects health care quality and causes elevation of health care costs 1,2 . The Food and Drug Administration (FDA) of the USA recorded 61 drug shortage incidents in 2005 which increased to 178 in 2010 3,4 .…”
Section: Introductionmentioning
confidence: 99%
“…Contributing factors to drug shortages may include manufacturing quality aspects e.g. contamination, regularity issues, business decisions or disturbances within the supply chain 1,2,6 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations